2018
DOI: 10.1002/jbmr.3531
|View full text |Cite
|
Sign up to set email alerts
|

Chiari I Malformation and Basilar Invagination in Fibrous Dysplasia: Prevalence, Mechanisms, and Clinical Implications

Abstract: Fibrous dysplasia (FD) is a mosaic disorder of benign fibro-osseous lesions, which may be associated with extraskeletal features as part of McCune-Albright syndrome (MAS). Cranial base abnormalities, including Chiari I malformation (CM1), in which the cerebellum extends below the foramen magnum, and secondary basilar invagination (BI), in which the odontoid prolapses into the posterior cranial fossa, are potentially serious complications of metabolic bone disorders. The purpose of this study was to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…[3][4][5] CMI is sometimes associated with syndromes that impair normal bone development, e.g., achondroplasia. 3,[6][7][8][9] We previously identified CMI and occult spinal dysraphism in 2 patients with EPAS1 gain-of-function syndrome. 10 Early somatic gain-of-function mutations in EPAS1 encoding the protein hypoxia-inducible factor-2α (HIF-2α) causes a syndrome characterized by multiple paragangliomas, somatostatinoma, and polycythemia.…”
mentioning
confidence: 99%
“…[3][4][5] CMI is sometimes associated with syndromes that impair normal bone development, e.g., achondroplasia. 3,[6][7][8][9] We previously identified CMI and occult spinal dysraphism in 2 patients with EPAS1 gain-of-function syndrome. 10 Early somatic gain-of-function mutations in EPAS1 encoding the protein hypoxia-inducible factor-2α (HIF-2α) causes a syndrome characterized by multiple paragangliomas, somatostatinoma, and polycythemia.…”
mentioning
confidence: 99%
“…Cranial base abnormalities in FD are of concern due to the potential risk of devastating neurologic sequela. A recent study of 158 patients with craniofacial FD found that 6.3% had Chiari I malformation, while 7.6 % had secondary basilar invagination [47].…”
Section: Skeletal Manifestationsmentioning
confidence: 99%
“…Due to the risk for cranial base abnormalities, a full neurologic exam should be performed regularly in patients with craniofacial FD, and the cranial base should be evaluated radiographically at school age and when symptomatic [47].…”
Section: Evaluation and Managementmentioning
confidence: 99%
“…[9] patient, a 14-year-old girl with polyostotic fibrous dysplasia, McCune–Albright syndrome and bilateral occipital aneurysmal bone cysts. The Pan et al [10] study clearly documents the propensity of the patients with craniofacial fibrous dysplasia toward basilar invagination and Chiari I malformation. Their detailed craniomorphometric evaluation suggests that Chiari I malformation stems from restriction of the posterior fossa volume.…”
Section: Discussionmentioning
confidence: 99%